Canadian Association of Gastroenterology Indicators of Safety Compromise following Colonoscopy in Clinical Practice. (21st June 2016) - Borgaonkar, Mark R.; Pace, David; Lougheed, Muna; Marcoux, Curtis; Evans, Bradley; Hickey, Nikita; O'Leary, Meghan; McGrath, Jerry
Abstract : In 2012 the Canadian Association of Gastroenterology published 19 indicators of safety compromise. We studied the incidence of these indicators by reviewing all colonoscopies performed in St. John's, NL, between January 1, 2012, and June 30, 2012. Results . A total of 3235 colonoscopies were included. Adverse events are as follows. Medication-related includes use of reversal agents 0.1%, hypoxia 9.9%, hypotension 15.4%, and hypertension 0.9%. No patients required CPR or experienced allergic reactions or laryngospasm/bronchospasm. The indicator, "sedation dosages in patients older than 70, " showed lower usage of fentanyl and midazolam in elderly patients. Procedure-related immediate includes perforation 0.2%, immediate postpolypectomy bleeding 0.3%, need for hospital admission or transfer to the emergency department 0.1%, and severe persistent abdominal pain proven not to be perforation 0.4%. Instrument impaction was not seen. Procedure-related delayed includes death within 14 days 0.1%, unplanned health care visit within 14 days of the colonoscopy 1.8%, unplanned hospitalization within 14 days of the colonoscopy 0.6%, bleeding within 14 days of colonoscopy 0.2%, infection 0.03%, and metabolic complication 0.03%. Conclusions . The most common adverse events were mild and sedation related. Rates of serious adverse events were in keeping with published reports.